Evaluation and follow-up of cognitive functions in patients with minor stroke and transient ischemic attack - Deniz C; Celik Y; Ozdemir Gultekin T; Eryigit Baran G; Deniz C; Asil T (Neuropsychiatric Disease and Treatment)
Çiğdem Deniz,1 Yahya Çelik,2 Tuğçe Özdemir Gültekin,1 Gozde Eryiğit Baran,1 Çağla Deniz,3 Talip Asil1 1Department of Neurology, Faculty of Medicine, Bezmialem Vakif University, İstanbul, 2Department of Neurology, Faculty of Medicine, Trakya University, Edirne, 3Department of Neurology, Avrupa Hospital, Adana, Turkey Background and purpose: We aimed to examine the incidence of cognitive impairment among patients with stroke, the associated risk factors, progression of the cognitive impairment, and the association between the localization of the lesion(s) as detected by magnetic resonance imaging and the affected areas of cognitive function. Methods: A total of 40 patients over 18 years of age enduring a transient ischemic stroke or minor stroke within the past 3 months who had a minimum life expectancy of 1 year were included in this study. Same number, age-, and sex-matched individuals were included as controls. Patients were inquired on the presence of risk factors for stroke. A series of neuropsychological test batteries were administered in patient and control subjects for assessing cognitive functions. These tests were readministered at 6 and 12 months of follow-up to assess the progression of cognitive functions. Results: In this study among the patients with stroke, a significant impairment was seen in multiple cognitive functional tests following ischemic stroke as compared to control groups. The most common risk factors for stroke included hypertension (72.5%), hyperlipidemia, and cigarette smoking. The number of cognitive domains with an impairment was highest (in four cognitive tests) among those with coronary artery disease and atrial fibrillation, followed by those who had a >50% stenosis in Doppler (three cognitive tests). These findings suggest that the frequency of risk factors associated with stroke does not correlate with the frequency of risk factors associated with cognitive dysfunction. The stroke localizations were classified among the patients with stroke and reviewed in accordance with cognitive impairment. Conclusion: Neuropsychological tests, clinical findings, and imaging studies should be used to document the poststroke cognitive dysfunction. Keywords: dementia, vascular dementia, cognitive impairment, neuropsychological assessment, vascular risk factors